2004
DOI: 10.1038/428138a
|View full text |Cite
|
Sign up to set email alerts
|

Creation of long-lasting blood vessels

Abstract: The construction of stable blood vessels is a fundamental challenge for tissue engineering in regenerative medicine. Although certain genes can be introduced into vascular cells to enhance their survival and proliferation, these manipulations may be oncogenic. We show here that a network of long-lasting blood vessels can be formed in mice by co-implantation of vascular endothelial cells and mesenchymal precursor cells, by-passing the need for risky genetic manipulations. These networks are stable and functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
483
3
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 649 publications
(512 citation statements)
references
References 10 publications
18
483
3
1
Order By: Relevance
“…[1][2][3][4][5] The vessel walls engineered under these conditions were found to be substantially similar to native vessels at both molecular and cellular levels. [2][3][4][5] These findings have generated considerable interest in the potential application of engineered blood vessels in regenerative medicine and cell-based revascularization therapies.…”
Section: Introductionmentioning
confidence: 84%
“…[1][2][3][4][5] The vessel walls engineered under these conditions were found to be substantially similar to native vessels at both molecular and cellular levels. [2][3][4][5] These findings have generated considerable interest in the potential application of engineered blood vessels in regenerative medicine and cell-based revascularization therapies.…”
Section: Introductionmentioning
confidence: 84%
“…There are two explicit mechanisms of blood vessel growth: vasculogenesis, the de novo formation of blood vessels by endothelial progenitor cells, and angiogenesis, the sprouting of new vessels from preexisting ones. For engineering of microvasculature within a 3-D cell laden biomaterial construct, many biological extracellular matrix (ECM) materials and cell co-cultures have been studied with respect to their vasculogenic potential [1][2][3][4]. Mimicking the embryonic environment for vasculogenesis is a popular strategy; for example, experiments on encapsulation of vascular progenitor cells within 3-D biological ECM have been undertaken, in which angioblasts and mesenchymal stem cells self-organize into a microvascular network and form a capillary bed [5].…”
Section: Introductionmentioning
confidence: 99%
“…However, the process of angiogenesis is an inherently slow process (estimates range from 100 mm to 1 mm per day (Mikos et al, 1993;Orr et al, 2003)), and the timely generation of a stable vascular network has long been identified as a fundamental challenge for tissue engineering (Koike et al, 2004). Because of the inherent constraints of vascular ingrowth, constructs of clinically relevant size may progressively become devoid of oxygen and nutrients in their centre upon implantation, which will be detrimental for cellular function and survival (Radisic et al, 2006;Scheufler et al, 2008).…”
Section: Hypoxia In Bone Tissue Engineeringmentioning
confidence: 99%
“…Upon implantation, this network then only has to anastomose to the host vasculature to establish perfusion. Indeed, many studies have shown that implanted endothelial cells can contribute to the blood vessels that are formed inside tissue-engineered constructs (Koike et al, 2004;Ma et al, 2014a;van Gastel et al, 2012). While promising, most approaches are still in an experimental stage with varying degrees of success, even in small defects (Kim and von Recum, 2008).…”
Section: The Potential Of Intrinsic Angiogenesis To Decrease Hypoxiamentioning
confidence: 99%